BDS Triple-frequency Medium and Long Baseline Ambiguity Resolution by Taking into Account of The Innospheric Delay Residuals. Issue 3 (February 2019) - Meng, Fanjun; Li, Shujun; Zhang, Jin; Yan, Lei
Abstract: In order to solve the shortcomings of the classic geometry-free TCAR algorithm in the process of the medium-long baseline ambiguity resolution, this paper puts forward the expression of the combined ambiguity standard deviation by considering the ionospheric delay residuals, tropospheric delay residuals, satellite orbital residuals and observation noise. It also comes up with the total noise level(TNL) of many optimal extra-wide lane(EWL), wide lane(WL) and narrow lane(NL) combinations based on the existing empirical value of each residual item under the condition of 100km, 100-200km and greater than 200km baseline length. Moreover, it proves that ionospheric delay residuals are the most dominant error source in the medium-long baseline carrier phase ambiguity resolution by analyzing the correlation between the total noise level(TNL) of each combination and its corresponding ionospheric delay residuals. Finally, it presents an ionospheric delay correction algorithm and then carries out experimental verification and feasibility analysis of the algorithm based on the beidou triple-frequency measured data. Results show that the fluctuation range of the NL float ambiguity can be reduced from 10 cycle to less than 1 cycle.